The effect of infrastructure development on urban-rural price differences in China - Glushenkova, Marina; Shi, Yingying (N/A, 2021)
Market liberalization reforms in China have given rise to greater domestic market integration. However, large urban-rural price differences indicate that the segregation of the urban and rural markets still exists in China. We study evolution of price differences between urban and rural areas across 25 Chinese provinces over the period of 1985 and 2018. First, we show that while there is an evidence of convergence separately for urban markets and for rural markets in China, the gap between urban and rural price levels within each province still remains large and persists over time. Second, we find that the urban-rural price gap has shrunk after 2000, when China adopted the Price Law resulted in liberalization of prices. This is suggestive of deeper urban-rural integration associated with policy changes. In addition, we record notable differences in urban-rural price gaps between provinces, however, using the log-t test we find an evidence of regional convergence of these price gaps. Finally, we investigate the effect of transport infrastructure development on the urban-rural price differences. The regression results show that highway- and railway-related variables have strong negative effect on the urban-rural price divide, indicating that infrastructure development is conducive to market integration between urban and rural areas in China. Therefore, further improvement of infrastructure can promote the process of urban-rural economic integration within Chinese provinces, and this could became a main focus of the China's rural revitalization strategy introduced in 2018.